Malacologic benthic fauna of the Socorro Island Littoral, Revillagigedo, Mexico - Mille-Pagaza, SR; Pérez-Chi, A; Holguín-Quiñones, O (Ciencias Marinas, 1994)
A survey on rocky shore mollusks was conducted in some bays of Socorro Island during February and May 1991 and March 1992. Specific richness and composition were analyzed for all expeditions. Relative density and frequency were analyzed only for the last two. The Importance Value Index (IVI) and Jaccard and Morisita similarity indexes were also calculated. Gastropods were the most diverse mollusks in the island, with 23 species in February, 33 in May and 39 in March. Vargas Lozano Bay had the highest total specific richness in all expeditions (25 in February, 30 in May and 33 in March) due to weak waves that produce greater bottom stability, and a great nutrient contribution from the ships that arrive to the island. Playa Blanca NE Bay showed the highest relative density in May (38.9%) and Playa Norte E Bay in March (24.1%). The IVI showed that the same species obtained the highest levels in all bays and expeditions. In May and March, Isognomon janus and Mitrella baccata were the most common species in all bays. Jaccard and Morisita indexes showed three principal assemblies. Grayson, Binners and Braithwaite were the most similar bays, characterized by strong waves and the presence of some tide pools on the shore. The second group consists of Vargas Lozano and Playa Blanca SO Bays which have protected rocky shores. Playa Blanca NE and Playa Norte E Bays form the third group because of their particular conditions; the first one has a well-developed coral reefnext to the beach, and the second one has a narrow supra and intertidal fringe.